Long-Term Tobacco Use and COPD Outcomes: A Systematic Review of Disease Progression, Smoking Cessation Benefits, and Treatment Modification - Shopia Mabella; Bayu Irianto (International Medical Journal Corp. Ltd, 2026)
Introduction: Smoking is the primary risk factor for chronic obstructive pulmonary disease (COPD), yet the quantitative impact of long-term smoking exposure on disease progression and the magnitude of benefit from cessation remain incompletely characterized. This systematic review synthesizes evidence from longitudinal studies to quantify the effects of smoking on COPD progression and evaluate how smoking status modifies treatment responses. Methods: We systematically screened longitudinal studies with ≥12 months follow-up examining smoking exposure in adults with established COPD. Studies were included if they reported quantitative measures of progression including FEV1 decline, exacerbation frequency, hospitalization, mortality, or quality of life. Data extraction encompassed smoking history, progression measures, long-term outcomes, study design, baseline characteristics, and effect modifiers. Results: Eighty studies with follow-up ranging from 6 months to 32.5 years were included. Current smokers exhibited accelerated FEV1 decline compared with former smokers, with excess decline ranging from 7-10 mL/year in general populations to >100 mL/year in genetically susceptible subgroups (p<0.001) (1,2). Smoking cessation produced immediate FEV1 improvement (121.8 mL at week 12, p=0.0069) that partially attenuated over time (20), with sustained symptom benefits (20,55). The half-life of excess COPD risk after quitting was 13.3 years (95% CI 11.86-14.96) (8). Smoking status significantly modified pharmacotherapy responses: current smokers showed blunted responses to inhaled corticosteroids (9,10,57), reduced benefit from azithromycin (interaction p=0.03) (11), but enhanced responses to CXCR2 antagonists (23). Exacerbations accelerated FEV1 decline by an additional 23 mL/year in GOLD stage 1, with smoking amplifying this effect (14). Mortality was significantly reduced with cessation in multiple studies (RR 0.75, 95% CI 0.56-1.00, p=0.05) (4). Discussion: This review demonstrates that continued smoking accelerates COPD progression through multiple mechanistic pathways including sustained neutrophilic inflammation, bacterial colonization, and corticosteroid resistance. Cessation benefits accumulate gradually over decades, with baseline severity and age at cessation as critical determinants of outcomes. The paradoxical early fall in CT lung density post-cessation reflects inflammatory resolution rather than emphysema worsening. Conclusion: Smoking cessation remains the cornerstone intervention for modifying COPD progression, with effects on lung function, exacerbations, and mortality that accumulate over years. Treatment selection must account for ongoing smoking exposure due to substantially altered pharmacotherapy efficacy.